2020
DOI: 10.1108/jadee-05-2020-0103
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing repurchase behavior and benchmarking brands: implications for salespersons in a personal selling context

Abstract: PurposeThis work reports on a study to measure tractor owners' (mostly farmers') repurchase behavior (RPB). While earlier studies have focused on the technical aspects of the tractors, none as yet have considered farmer intention and behavior for predicting purchase decision. A conceptual model was built considering all possible antecedents of farmers' RPB based on in-depth interviews and discussions with marketing managers. Interviews with customers were used to understand these antecedents or interactions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The more associations that a consumer stores in his/her mind, the greater the extent of an individual's knowledge about the brand, and the stronger the brand is; this increases the number of pathways between associations and increases the likelihood of being recalled in several situations (French and Smith, 2013), such as purchase decisions, or conversations with other consumers. Mohanty and Patro (2020) found that farmers' perceptions about agricultural equipment brands (brand associations) were a significant predictor of repurchase behavior. Based on these arguments and evidence, the following hypotheses are developed: H2.1.…”
Section: Recommendation and Repurchase: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The more associations that a consumer stores in his/her mind, the greater the extent of an individual's knowledge about the brand, and the stronger the brand is; this increases the number of pathways between associations and increases the likelihood of being recalled in several situations (French and Smith, 2013), such as purchase decisions, or conversations with other consumers. Mohanty and Patro (2020) found that farmers' perceptions about agricultural equipment brands (brand associations) were a significant predictor of repurchase behavior. Based on these arguments and evidence, the following hypotheses are developed: H2.1.…”
Section: Recommendation and Repurchase: Hypotheses Developmentmentioning
confidence: 99%
“…A good evaluation of the brand in the purchase determinants generates preference toward the brand and positive behaviors such as recommending and repurchasing it (Keller and Lehman, 2006;Buil et al, 2013). In a study regarding agricultural equipment (Mohanty and Patro, 2020), repurchase decision of farmers was mainly driven by functional characteristics of equipment (mileage, design, dependency, power, pickup, overall performance, accessories, seat position, extra functions, clutch plate, noise level, oil change). Other economic and hedonic aspects were also part of farmers experience as a predictor of repurchase behavior.…”
Section: Recommendation and Repurchase: Hypotheses Developmentmentioning
confidence: 99%